The Roles of Nurse Educators and the Use of Web-Based Tools Suitable for Learner-Centered Learning Strategies in Distance Education in the Pandemic Process - Havva ARSLAN YURUMEZOGLU; Hale SEZER; Deniz SANLI; Hulya OKUMUS (Atatürk University, 2021)
One of the areas most affected by the COVID-19 pandemic has been nursing education. This process not only has created many difficulties, but also has provided the educators with the opportunity to revise existing traditional education. Especially current problems such as providing motivation for learners and involving learners in the learning process in traditional face-to-face education have been discussed in the distance education process much more. In this context, for a learner-centered nursing education, there has been a process in which some educator roles have come to the fore. In addition, it has become important to the use of web-based tools compatible for learner-centered teaching strategies. In this article, it is aimed to contribute to the maintenance of quality in distance education, which will partially continue in education programs after the pandemic, by providing a framework on the roles of educators, learner-centered learning strategies and the use of suitable tools for these in distance education in nursing education.